Nomenclatural notes on Sorbus vestita (Rosaceae) (Bangladesh Journal of Plant Taxonomy, 2013)
Not available.DOI: http://dx.doi.org/10.3329/bjpt.v20i2.17400Bangladesh J. Plant Taxon. 20(2): 251-253, 2013